The answer is 13 because you add.
Answer:
x = -8
Step-by-step explanation:
16+6-6x-4=-7x+3+7
Combine like terms
18 -6x = -7x+10
Add 7x to each side
18-6x+7x = -7x+7x+10
18+x = 10
Subtract 18 from each side
18+x-18 = 10-18
x = -8
Answer:
i)
\frac{3}{5} + (- \frac{1}{2}) = \frac{6}{10} - \frac{5}{10} = \frac{1}{10}
ii)
4^{3} + 8^{2} + \sqrt{9}
iii)
(\frac{4}{5})^{2}. \sqrt[3]{8} \leqx^{3} - 3x + 6 \leq \sqrt{\frac{1}{3}}
Step-by-step explanation:
i)
\frac{3}{5} + (- \frac{1}{2}) = \frac{6}{10} - \frac{5}{10} = \frac{1}{10}
ii)
4^{3} + 8^{2} + \sqrt{9}
iii)
(\frac{4}{5})^{2}. \sqrt[3]{8} \leqx^{3} - 3x + 6 \leq \sqrt{\frac{1}{3}}
Assuming the input is x:
y= (6.5)(x) - 9.5
substitute 4 in for x
y= (6.5)(4) - 9.5
multiply sets of parentheses
y= 26 - 9.5
y= 16.5
ANSWER: The output value is 16.5 (second answer down).
Hope this helps! :)